The raw material preferences for producing picture stones on Gotland - Hänsel, Patrick; Oehrl, Sigmund; Widerström, Per; Ideström, Lena; Munnecke, Axel (Fornvännen. Journal of Swedish Antiquarian Research, 2024)
The picture stones on Gotland are monuments from the late Scandinavian Iron Age, which are important for the archaeological research about the North Germanic culture. Their imagery is also a valuable source for the pre-Christian religion in Scandinavia. Most of them are produced of Silurian limestones which are dated 423 to 433 million years. The Gotlandic picture stones were produced of thickly bedded limestones which are exposed in the vicinity of fossil reefs and carbonate platforms. Archaeologically, the picture stones can be classified into five groups (A to E stones), and an informal sixth group (so-called blind C/D/E stones). Geologically, the picture stone raw materials can be sorted into six different types based on visual facies analysis. The purpose of our paper is to investigate the raw material preferences for single picture stone types. According to our results, coarse and fine reef debris limestones were the most frequently used rock types. For the B stones, crinoidal limestone was preferentially used because of its sparkling effect of the crinoid remains in sunlight. However, the availability of nearby thickly bedded limestones was the most important prerequisite to produce most of the picture stone
Keywords: crinoidal limestone; Gotland; picture stones; raw material preferences; reef debris limestone